(untitled) (Al-Farooq Journal of Sciences, 2026)
This research examines the relationship between international human rights law and epidemics, with a particular focus on the right to health as a fundamental entitlement recognized in international instruments. The study begins with a conceptual framework that defines international human rights law and epidemics, then explores the legal foundations of the right to health through the Universal Declaration of Human Rights (1948), the International Covenant on Economic, Social and Cultural Rights (1966), and specialized conventions addressing vulnerable groups. The analysis highlights the obligations of states during epidemics, including the duty to protect the right to health, the legitimacy of restrictions on rights and freedoms, the necessity of international cooperation, and the protection of vulnerable populations. It emphasizes that restrictions imposed during health emergencies must comply with principles of legality, necessity, proportionality, and non-discrimination, while ensuring transparency and accountability. A comparative perspective is provided by examining European and Arab experiences during the COVID-19 pandemic, revealing differences in judicial oversight, transparency, and protection of marginalized groups. The study also identifies future challenges for international human rights law in managing epidemics, such as balancing public health and individual rights, ensuring health equity, strengthening international cooperation, safeguarding digital privacy, and securing sustainable health financing. The findings confirm that epidemics are not merely health crises but also legal and human rights challenges. Lessons from COVID-19 demonstrate that respect for human rights principles enhances the effectiveness of health responses and strengthens public trust, while neglecting them undermines legitimacy and exacerbates crises. The research concludes that building a more flexible and equitable international legal framework is essential to confront future epidemics while preserving human dignity and fundamental rights.